2022
DOI: 10.1007/s00405-022-07385-9
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-based nystagmus diagnostics: development of an innovative app for the targeted detection of vertigo

Abstract: Background In medicine, the symptom of dizziness is one of the most common multidisciplinary causes of emergency medical presentation. Attending physicians are often faced with difficult decisions when evaluating patients with dizziness. A rapid differential diagnostic decision must be made during the initial examination. The goal of this study, was to develop a smartphone-based app that can diagnose and qualify nystagmus. The app should enable differentiation between acute emergencies such as st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Among the 20 studies that reported the use of a device or app, 2 were related to anamnesis and subjective symptoms [ 3 , 8 ], 12 were related to objective examination [ 8 - 19 ], 7 were related to remote diagnosis [ 9 , 11 , 15 , 16 , 18 , 20 ], and 7 were related to treatment and rehabilitation [ 20 - 26 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the 20 studies that reported the use of a device or app, 2 were related to anamnesis and subjective symptoms [ 3 , 8 ], 12 were related to objective examination [ 8 - 19 ], 7 were related to remote diagnosis [ 9 , 11 , 15 , 16 , 18 , 20 ], and 7 were related to treatment and rehabilitation [ 20 - 26 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three papers used virtual reality (VR) for treatment with the Epley maneuver [ 21 ] and vestibular rehabilitation [ 23 , 26 ]. Eight papers included apps or devices with more than one category of medical act performed; all papers were about sequential acts [ 8 , 9 , 11 , 12 , 15 , 16 , 18 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…KI-gestützte Analysen von vHIT, Videooculografie und Posturografie ermöglichen eine Unterteilung 69 . Als Weiterentwicklung daraus erfolgt die Erstellung von Apps, mit deren Hilfe in Akutsituationen durch klinische Tests oder Auswertung von Nystagmus-Formen Diagnosen verifiziert werden können 70 . Die Unterscheidung episodischer Schwindelanfälle in M. Mèniere oder eine vestibuläre Migräne kann in symptomfreien Intervallen schwierig sein.…”
Section: Künstliche Intelligenz In Teilgebieten Der Neurologieunclassified